Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Rodriguez Velarde, Jose Luis (2019)
The present work entitled "Analysis, diagnosis and formulation of strategies for a leading company in the Peruvian agribusiness sector" was prepared with the intention of being able to provide recommendations of a strategic nature that allow a better development, growth and improvement of competitiveness for the company "Camposol” in the agribusiness sector. “Camposol”, an agribusiness company, began operations in 1997, with the purchase of its first land in La Libertad, a region located in northern Peru, 600 km from Lima. Nowadays Camposol is already one of the main producers and exporters of avocado, blueberries, grapes, mangoes, tangerines and prawns. Likewise, it has a high international recognition, revenues of more than US $ 340 million annually and with more than 14 thousand workers, making it one of the main employer companies in Peru.The elaboration of the action plan for the company includes the development of the following topics: First, a strategic diagnosis will be made based on the analysis of the company's business model, which will allow us to understand its organizational structure, key activities, strengths, weaknesses and competitive advantages. This analysis will then be aligned with respect to adverse factors to the company, identifying opportunities, threats and the level of business rivalry within the sector in which it operates.Once the strategic diagnosis has been made, an action plan will be developed based on strategy formulation. These strategies will be aimed at a global, corporate, business and functional level, also defining the mission, vision and objectives to be achieved with their implementation.After formulating the most convenient strategies for Camposol, the new form of organizational structure that the company should have in order to facilitate its implementation will be proposed. This new structure will be the result of the analysis of the creation of new strategic business units that adapt to the proposed objectives and the business vision.Finally, a control plan will be developed to measure the correct implementation of the strategies and the fulfillment of objectives, including a series of conclusions and recommendations to be taken into account to maintain competitiveness in the different markets in which it operates.